Addressing Climate Change Risks Influencing Cryosphere-Fed Kuhl Irrigation System in the Upper Indus Basin of Pakistan - Ashraf, Arshad; Akbar, Ghani (International Journal of Environment, 2020)
Cryosphere-fed kuhl irrigation system forms a major lifeline for agriculture and livelihood development in the Himalayan region. The system is highly vulnerable to climate change impacts like glacier retreat, glacial lake outburst floods, snow avalanches and landslides especially in the upper Indus Basin (UIB). It is necessary to conduct reassessment of climate change impacts and find coping strategies for sustainable agriculture development in this mountainous region. In the present study, risks of glacier depletion , lakes outburst flood, snow avalanche and landslide hazards impacting cryosphere-fed kuhl irrigation system in 10 river basins of the UIB of Pakistan were analyzed using multi-hazard indexing approach. High risk of glacier depletion was observed in the Astore and Swat river basins likely because of the combined effect of reduced snow precipitation and rising warm temperatures in these basins. The risk of expansion in aggregate lake area was high in the Indus sub-basin, moderate in the five basins (i.e., Hunza, Shigar, Shyok, Shingo and Astore), while it was low in the four basins (i.e., Swat, Chitral, Gilgit and Jhelum). More than 2% areas of Hunza and Shigar basins in the Karakoram range exhibited high risk of snow avalanche and landslide (SAL) hazard, while moderate SAL hazard was found in >40% areas of Chitral, Gilgit, Hunza and Shigar river basins. An effective early warning mechanism and provision of adequate resources for preparedness are essential to cope with negative impacts of climate change on irrigated agriculture in this region in future.